Effect of cigarette smoking cessation educational intervention based on the trans-theoretical model using motivational interviewing on Egyptian males' smoking knowledge and behavior: A randomized controlled trial - Samiha Hamdi Sayed; Sahar Mohammed El-Sakkar; Sabreen Ahmed Elsaka; Amira Abdallah El-Houfey (Tehran University of Medical Sciences, 2023)
Background & Aim: The trans-theoretical model suggests that stage-matched interventions improve the effectiveness of behavior changes such as quitting. This study aims to examine the effect of stage-matched smoking cessation educational intervention based on the trans-theoretical model using motivational interviewing on Egyptian males' knowledge, stage movement, and smoking cessation rate. Methods & Materials: A randomized controlled trial was conducted in the main building of Damanhour University, Egypt. The participants were selected using simple random sampling (N=165), then allocated to both experimental (N=82) and control (N=83) groups using the randomization block technique. Data was collected using a structured interview schedule. The instrument contained five parts: Personal Characteristics and Smoking data, Fagerstrom Tolerance Questionnaire, Tobacco Cessation Readiness Scale, Smoking Knowledge Scale, and trans-theoretical Model constructs questionnaire. The experimental group received ten months of educational intervention using face-to-face and phone-based motivational interviewing. Results: A significantly higher stage movement was revealed among the experimental group post-intervention (80.5%); 35.4% transitioned to the preparation stage, 32.9% were in the action stage, and 12.2% were in the maintenance stage. According to the ANCOVA test, significant negative mean differences post-intervention was achieved for nicotine dependence and decision pros (P=0.000) with a large effect size (η2=0.341, η2=0.503). However, significant positive mean differences were proved for other variables (knowledge, tobacco cessation readiness, and TTM constructs) (P<0.05) with a large effect size (η2>0.14). Stage analysis revealed significant mean differences in most studied variables, where the action stage had the highest significant mean improvements (P<0.05). Conclusion: The trans-theoretical model-based educational intervention using motivational interviewing effectively improves smoking knowledge and facilitates quitting with successful stage movement among Egyptian male smokers.